The emotionally focused casebook : new directions in treating couples - Furrow, James L.; Johnson, Susan M.; Bradley, Brent A. (New York, NY : Routledge, 2011)
'There is currently no single resource that compiles the various applications to the many clinical populations being served by EFT today. The Emotionally Focused Casebook fills that void as a substantive reference for clinicians, students, professors, and supervisors using and teaching EFT. Each chapter utilizes a hands-on case study approach with concrete guidelines and illustrations for the adaptation and application of EFT with specific treatment populations. This casebook is the perfect practical resource for professionals and students looking for examples of specific theoretical, conceptual, and treatment applications of EFT'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Couples therapy -- Case studies; Emotion-focused therapy -- Case studies; Couples Therapy -- methods -- case reports; Marital Therapy -- methods -- case reports